Assessing soil conservation techniques on sloping lands in the humid tropics area of Indonesia in the context of maize cultivation - RISMA NESWATI; SOFYAN ABDULLAH; YUNUS MUSA; NASARUDDIN NASARUDDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Neswati R, Abdullah S, Musa Y, Nasaruddin. 2023. Assessing soil conservation techniques on sloping lands in the humid tropics area of Indonesia in the context of maize cultivation. Biodiversitas 24: 1686-1692. Sloping land is prone to severe erosion, particularly in areas with high precipitation, such as in humid tropics. In addition to slope and rain factors, crop management also influences soil erosion. This research aims to identify the most appropriate techniques to mitigate soil erosion by comparing three different techniques of maize (Zea mays L.) cultivation planted on sloping land in Indonesia's humid tropics. A field experiment was conducted in Gorontalo Regency, Gorontalo Province, Indonesia, in three maize growing seasons at a location with a slope of 15-30%. We used a split-plot design in a randomized block design, with the main factor being conservation techniques, namely no treatment (control) (K0), contour terrace (K1), strip cropping using Pennisetum purpureum Schumach. (K2) and alley cropping using Gliricidia sepium (Jacq.) Kunth (K3), and the side factor was Z. mays of two varieties: Mixed variety Arjuna BC (H1) and hybrid variety NK-33 (H2). The effects of each treatment were measured in term of soil erosion, and maize growth and productivity. The results showed that the strip cropping resulted in a lower erosion level compared to the contour terrace and alley cropping. However, erosion still exceeded the tolerable soil loss in all conservation techniques. The effects on the growth and production of maize of the two varieties in growing seasons 1, 2, and 3 were not statistically different (p<0.05). Maize production can reach >6 tons ha-1 in the two varieties planted and the value of the revenue to cost (R/C) ratio of all treatments ranged between 1.77 and 2.54. The results imply that the application of appropriate soil conservation methods has the potential to reduce erosion in the sloping land-humid tropics of Indonesia without compromising growth and productivity. However, it will take a longer period to reduce soil erosion significantly in a maize-based cultivation system on sloping land.